2019
DOI: 10.1021/acssuschemeng.8b05993
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Porous Catalysts Derived from Metal–Organic Framework for Oxygen Reduction Reaction in an Anion Exchange Membrane Fuel Cell

Abstract: obvious degradation, even after potential cycling of half-cell measurement (30 000 cycles). The prepared material exhibited a porous structure composed of nanoparticles (NPs) that were randomly distributed on poly-hydrocarbon structures with a Brunauer−Emmett−Teller surface area of 449.0 m 2 g −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…The single cell performance of the prepared AEMs was measured at 60 °C in comparison with the Fumion-FAA-3 ionomer membrane (FAA-3-IM), and the results are shown in Figure a. The open circuit voltage (OCV) of all AEMs was greater than 0.96 V, indicating weak fuel gas permeability. The power density of PYR-PAE-PhPh and PYR-PAE-BPHF was 109 mW cm –2 and 89 mW cm –2 , respectively. Meanwhile, the peak power density of FAA-3-IM (30 mW cm –2 ) was lower than that of the as-synthesized AEMs.…”
Section: Resultsmentioning
confidence: 99%
“…The single cell performance of the prepared AEMs was measured at 60 °C in comparison with the Fumion-FAA-3 ionomer membrane (FAA-3-IM), and the results are shown in Figure a. The open circuit voltage (OCV) of all AEMs was greater than 0.96 V, indicating weak fuel gas permeability. The power density of PYR-PAE-PhPh and PYR-PAE-BPHF was 109 mW cm –2 and 89 mW cm –2 , respectively. Meanwhile, the peak power density of FAA-3-IM (30 mW cm –2 ) was lower than that of the as-synthesized AEMs.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the best performing mass loading of M–N–C catalysts in membrane electrode assemblies (MEAs) are generally range from 2 to 3 mg cm −2 . [ 49–51 ] However, the performance of our Co 1 /CNH 700 catalyst continues to with the loading amount of the catalyst, and the loading amount for its best performance is 6.0 mg cm −2 . It is believed that the 3D radial shape and porous nature of Co 1 /CNH 700 effectively facilitates the mass transfer of reactants and products, leading to the high utilization of active sites even in thick catalyst layers (Figure S19, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, interfacing TMOs with metallic and conductive porous (nano)carbon phases is also advantageous for the anodic HOR, especially considering the sluggish HOR kinetics in alkaline medium. Accordingly, multicomponent systems are highly in demand for AEMFCs, which benefit from PGM-free electrocatalyst nanomaterials with promising stabilities under alkaline conditions. , Because ideal alkaline HOR catalysts should have both optimal hydroxyl- and hydrogen-binding energies, oxophilic surfaces developed by structural engineering can significantly boost HOR kinetics via increasing the number of active sites for the optimum adsorption of H* and OH* intermediate species. , Yang et al reported CeO 2 @Ni@C as a highly efficient HOR electrocatalyst for AEMFCs . They observed that the enhancement in the electron transfer between CeO 2 and Ni phases in the heterostructure led to thermoneutral adsorption free energies of H* with an optimal Δ G H * on the Ni surface, while the oxygen-vacancy-rich CeO 2 promoted the adsorption strength of OH* species.…”
Section: Nanomaterial-based Systems For Electrochemical Energy Conver...mentioning
confidence: 99%